2011
DOI: 10.1038/nri3062
|View full text |Cite
|
Sign up to set email alerts
|

Inflammatory modulation of HSCs: viewing the HSC as a foundation for the immune response

Abstract: Preface Cells of the innate and adaptive immune systems are the progeny of a variety of hematopoietic precursors, the most primitive of which is the hematopoietic stem cell. Hematopoietic stem cells have been thought of generally as dormant cells that are only called upon to divide under extreme conditions, such as marrow ablation through radiation or chemotherapy. However, recent studies suggest that hematopoietic stem cells respond directly and immediately to infections and inflammatory signals. In this Revi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

11
502
1
2

Year Published

2012
2012
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 488 publications
(516 citation statements)
references
References 60 publications
11
502
1
2
Order By: Relevance
“…It is a recent notion only that HSCs and multipotent progenitors themselves can be activated via feedback-loops in response to stress (5,85). In addition, they seem to have intrinsic machinery for defense against attacking bacterial or viral pathogens (86). The robust self-protective signatures of LS ϩ K and LS Ϫ K presented in this study, for the first time enable us to dissect the utilization of distinct immune mechanisms along differentiation on a comprehensive protein level.…”
Section: Distinct Self-protective Signatures In Multipotent Ls ϩ K Anmentioning
confidence: 89%
“…It is a recent notion only that HSCs and multipotent progenitors themselves can be activated via feedback-loops in response to stress (5,85). In addition, they seem to have intrinsic machinery for defense against attacking bacterial or viral pathogens (86). The robust self-protective signatures of LS ϩ K and LS Ϫ K presented in this study, for the first time enable us to dissect the utilization of distinct immune mechanisms along differentiation on a comprehensive protein level.…”
Section: Distinct Self-protective Signatures In Multipotent Ls ϩ K Anmentioning
confidence: 89%
“…It is possible that, in sss P1 flies, the activation of GSC divisions results from an increased immune response caused by extended wake. Although the regulation of stem cell function by the immunological status of the organism is not yet completely understood, mitotic activity in stem cell populations is affected by bacterial infection and inflammation in both mammalian and fly tissues (44)(45)(46)(47). Alternatively, oxidative stress could contribute to the altered stem cell activity in sss mutants.…”
Section: Discussionmentioning
confidence: 99%
“…16). For instance, a number of laboratories reported that LPS-induced signaling through TLR4 (14, 43) and proinflammatory mediators, such as IFN (44,45), can modulate LT-HSC function, with particular emphasis on their self-renewal potential and subsequent ability to differentiate into downstream progenitors.…”
Section: Discussionmentioning
confidence: 99%
“…LT-HSCs are multipotent cells capable of providing long-term replenishment of the entire hematopoietic pathway (11). Although LT-HSCs are viewed as a critical component in the response to infection or inflammation (12,13), a number of studies described the long-term impact of inflammation on the function of LT-HSCs in terms of their ability to self-renew, engraft, and differentiate (14)(15)(16). It remains less well understood whether inflammation-associated alterations to LT-HSCs can also affect the function of downstream leukocytes and, of particular interest in our studies, DCs.…”
mentioning
confidence: 99%